Dialoguing and Questioning Are Critical for the Development of Understanding and Knowledge. - Ozcan, Suna (American Annals of the Deaf)
This editorial focuses on the critical role of dialoguing and questioning in advancing understanding and knowledge within educational and research contexts. It emphasizes that teachers and students benefit from engaging in dialogue and inquiry to foster higher-order thinking, motivation, and collaborative knowledge construction, while also addressing challenges such as misinformation. In research, collaborations among academic researchers, educators, and participants—often involving diverse perspectives—enhance the validity and applicability of findings, bridging theoretical and practical knowledge through dialogic methodologies. The article highlights that interdisciplinary and critical dialogue among researchers promotes intellectual humility, innovation, and the democratization of knowledge, countering disciplinary silos and supporting ongoing scientific renewal. Overall, dialoguing and questioning are presented as fundamental epistemological and ethical necessities for inquiry-based learning, research collaboration, and the respectful exchange of ideas in diverse cultural and academic settings.